КЛИНИКО-ЭПИДЕМИОЛОГИЧЕСКАЯ ХАРАКТЕРИСТИКА ДЕТСКОГО ТУБЕРКУЛЕЗА В САНКТ-ПЕТЕРБУРГЕ НАКАНУНЕ ПАНДЕМИИ COVID-19 И ПРИ ЕЕ РАЗВИТИИ - Лозовская, Марина Эдуардовна; Захарова, Ольга Павловна; Гросова, Анастасия Витальевна; Зинкевич, Виктория Алексеевна (FORCIPE, 2022)